The Role of Gratitude and Forgiveness on Subjective Wellbeing in Employees Who Have Experienced Layoffs - Prabhadi Nusantara; Ferdinandus Hindiarto (Green Publisher Indonesia, 2025)
The COVID-19 pandemic has led to a decline in global socio-economic conditions, including a surge in unemployment, which has impacted individuals' low subjective wellbeing (SWB). This study aims to analyze the effect of forgiveness and gratitude on SWB in employees who have experienced termination of employment (PHK), focusing on a unique context in Semarang, Indonesia. The research used a correlational quantitative approach with a sample of 402 employees selected through purposive sampling. SWB variables were measured using the Satisfaction with Life Scale (SWLS) and Positive Affect Negative Affect Schedule (PANAS) scales. In contrast, gratitude and forgiveness were calculated using the Gratitude Questionnaire (GQ-6) and a scale based on avoidance, revenge, and benevolence motivation aspects. Data analysis was carried out using multiple linear regression and product-moment correlation. The results showed that forgiveness and gratitude significantly affected SWB (20.8% effective contribution), with gratitude as the dominant factor. The SWB and gratitude categories were moderate, while forgiveness was relatively high, indicating the positive adaptability of participants, even though they had experienced layoffs. The implications of this study emphasize the importance of forgiveness and gratitude-based psychological interventions to improve the mental well-being of post-layoff vulnerable groups, as well as recommendations for follow-up research with a more diverse sample and measurement time closer to the incidence of layoffs.